5,6,7,4’-tetramethoxyflavanone protects against neuronal degeneration induced by dexamethasone by attenuating amyloidogenesis in mice - Kanet Pakdeepak (2020)
© 2020, Leibniz Research Centre for Working Environment and Human Factors. All rights reserved. Long-term exposure to high glucocorticoid levels induces memory impairment and neurodegeneration in Alzheimer’s disease (AD) by increasing the expression of amyloid β and tau hyperphosphorylation (pTau). Previous studies showed beneficial effects of flavonoids in neurodegenerative models. 5,6,7,4'-tetramethoxyflavanone (TMF) is one of the active ingredients in Chromolaena odorata (L.), which R. M. King and H. Rob discovered in Thailand. This study focused on the effects of TMF on dexamethasone (DEX)-induced neurodegeneration, amyloidogenesis, pTau expression, neuron synaptic function, and cognitive impairment and the potential mechanisms involved. Mice were intraperitoneally administered DEX for 28 days before being treated with TMF for 30 days. The mice were randomly divided into six groups (twelve mice per group): control; TMF administration (40 mg/kg); pioglitazone administration (20 mg/kg); DEX administration (60 mg/kg); DEX administration plus TMF; and DEX administration plus pioglitazone. Behavioral tests showed that TMF significantly attenuated the memory impairment triggered by DEX. Consistently, TMF reduced DEX-induced amyloid beta production by reducing the expression of beta-site APP cleaving enzyme 1 (BACE1) and presenilin 1 (PS1), whereas it increased the gene expression of a disintegrin and metalloprotease 10 (ADAM10). TMF treatment also decreased pTau expression, inhibited phosphonuclear factor-kappa B (pNF-kB) and inhibited glycogen synthase kinase 3 (GSK-3) activity by increasing GSK3 phosphorylation (pGSK3). In addition, TMF also improved synaptic function by increasing the expression of synaptophysin (Syn) and postsynaptic density protein 95 (PSD95) while decreasing acetylcholine esterase activity. Conclusively, TMF provided neuroprotection against DEX-induced neurodegeneration. These findings suggest that TMF might have potential as a therapeutic drug for AD.